2005
DOI: 10.1016/s1726-4901(09)70231-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Management and Prognostic Factors in Patients with Probable Severe Acute Respiratory Syndrome (SARS) in a SARS Center in Taiwan

Abstract: All patients with probable SARS who were admitted to hospital presented with fever and lymphopenia. While the efficacy of different treatments could not be evaluated from this retrospective study, a higher value of C-reactive protein was associated with the development of respiratory failure and subsequent intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
21
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 25 publications
7
21
2
Order By: Relevance
“…22 CRP can act directly on endothelial cells to increase levels of ICAM-1, VCAM-1, and MCP-1 expression, inducing a vascular inflammatory response, 26 thus promoting multiple organ failure and patient mortality. 28 Other studies have indicated that higher levels of CRP were associated with risk of multiple organ failure and mortality in critically ill patients. 27 Higher levels of CRP have been shown to be associated with respiratory failure and prolonged mechanical ventilation in Taiwan.…”
Section: Discussionmentioning
confidence: 97%
“…22 CRP can act directly on endothelial cells to increase levels of ICAM-1, VCAM-1, and MCP-1 expression, inducing a vascular inflammatory response, 26 thus promoting multiple organ failure and patient mortality. 28 Other studies have indicated that higher levels of CRP were associated with risk of multiple organ failure and mortality in critically ill patients. 27 Higher levels of CRP have been shown to be associated with respiratory failure and prolonged mechanical ventilation in Taiwan.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical presentations associated with MERS-CoV infection ranged from mild to fulminant, similar to severe acute respiratory syndrome (SARS) (91011). The initial symptoms in the most MERS cases were nonspecific fever, usually accompanied by cough, sore throat, myalgia, headache, and diarrhea.…”
mentioning
confidence: 99%
“…Furthermore, there were few reports regarding specific laboratory features as predictors for MERS-CoV infection in acute febrile patients without pneumonia during the nosocomial outbreak. Several studies reported that initial laboratory results including normal WBC with lymphopenia and thrombocytopenia were common among SARS patients (10111314). These laboratory features allowed early classification of febrile patients into likely and unlikely SARS group to utilize limited isolation facilities effectively (910111314).…”
mentioning
confidence: 99%
“…These clinical findings are similar to other reports, except that a higher percentage of patients had diarrhea at presentation; the latter finding differs from reports in other countries, but is similar to another report from Taiwan. 6 In the report of Liu et al, 7 underlying disease, which might explain the low fatality rate that was documented. In many other reports, the proportion of patients with various major underlying diseases was greater, such that the prognosis was worse once patients got SARS.…”
mentioning
confidence: 99%
“…Liu et al reported clinical characteristics, management, and analysis of prognostic factors in patients with probable SARS who were treated at a specially designated hospital in Taipei City during the SARS epidemic from late April to July 2003. 7 The number of cases included in the analysis was small. However, as only patients with suspected SARS (patients without pneumonia) were transferred to the investigators' hospital during the early epidemic, the clinicians may have been able to observe clinical pictures and disease progression in SARS patients without pneumonia during the early disease course.…”
mentioning
confidence: 99%